If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 = 5(u + -3) + 3u Reorder the terms: 9 = 5(-3 + u) + 3u 9 = (-3 * 5 + u * 5) + 3u 9 = (-15 + 5u) + 3u Combine like terms: 5u + 3u = 8u 9 = -15 + 8u Solving 9 = -15 + 8u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-8u' to each side of the equation. 9 + -8u = -15 + 8u + -8u Combine like terms: 8u + -8u = 0 9 + -8u = -15 + 0 9 + -8u = -15 Add '-9' to each side of the equation. 9 + -9 + -8u = -15 + -9 Combine like terms: 9 + -9 = 0 0 + -8u = -15 + -9 -8u = -15 + -9 Combine like terms: -15 + -9 = -24 -8u = -24 Divide each side by '-8'. u = 3 Simplifying u = 3
| 28=4(w+6)-6w | | 1/9a=6 | | 6(-2-x)=-5(x+3) | | 5x-4-3x=14 | | -4=n | | 4e^3x+2=110 | | 10(s-4)=-132 | | 4e^3x+2=20 | | 10(s-4)=3 | | 10/3(10) | | 4e^3x-2=110 | | 2/3=7/x-4 | | -7-15x=23 | | 0.2+x=3 | | 2x+3y+6z=98 | | 60x=-32 | | 82=14+2x | | -5(7x+10)=-295 | | 3/4p=114 | | 26/x=13/8 | | y=x^2-17/2 | | 2c+5=3c | | 17x-4=4(4x+5)-16 | | 2c+5=8c | | 4c+6=6c | | 4c+6=6 | | 10x(8x^3+1)=0 | | log(x/5)=3 | | x+9=8+4 | | 32-5q=-100 | | 40x+65=325 | | x^2=4y-3+7 |